Achieving rapid actuation in liquid crystal elastomers - Liu Changyue; Jin Liuchao; Liao Wei-Hsin; Wang Zhijian; He Qiguang (National Science Open)
Liquid crystal elastomer (LCE) is one kind of soft actuating material capable of producing large and reversible actuation strain, versatile and programmable actuation modes, and high work density, which can be widely exploited for next-generation soft robots. However, the slow response speed and low power density in LCE-based actuators remain a challenge, limiting their practical applications. Researchers have been considering how to improve these performances. In this review, we discuss the fundamentals of the LCEs and emphasize the fast actuation strategies developed in recent years. Initially, we introduce conventional preparation strategies. Then, we describe typical actuation mechanisms of LCEs, discussing their features and limitations. Subsequently, we summarize several possible approaches as case studies to enhance the actuation performance of LCEs, including reducing physical sizes, introducing active heating-cooling mechanisms, utilizing mechanical instability, and developing dielectric LCEs. Finally, we discuss the future research opportunities and challenges for rapid actuation of LCEs.